2003
DOI: 10.1080/1462220031000158708
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of self-report measures of nicotine dependence among male drug/alcohol-dependent cigarette smokers

Abstract: This study examined the psychometric properties and validity of the Fagerström Tolerance Questionnaire (FTQ), the Fagerström Test for Nicotine Dependence (FTND), and the Heaviness of Smoking Index (HSI) when used as self-report measures of nicotine dependence among male drug/alcohol-dependent smokers (n=191 participants in a large stop-smoking study). All three measures had fairly low internal consistency. The FTQ and FTND had similar two-factor structures, but the FTND factor structure accounted for a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The (problematic) use of other substances included 12-month alcohol use and alcohol-related problems measured with the Alcohol Use Disorders Identification Test [AUDIT: [42]] and a measure of smoking and smoking-related problems in the past four weeks using the Heaviness of Smoking Index [HSI: [43]]. Finally, any 12-month use of ecstasy, cocaine or amphetamines was assessed using an ad hoc questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The (problematic) use of other substances included 12-month alcohol use and alcohol-related problems measured with the Alcohol Use Disorders Identification Test [AUDIT: [42]] and a measure of smoking and smoking-related problems in the past four weeks using the Heaviness of Smoking Index [HSI: [43]]. Finally, any 12-month use of ecstasy, cocaine or amphetamines was assessed using an ad hoc questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…As a demonstration of predictive validity, we expect that higher scores of these measures would be associated inversely with cessation. The most widely used measure of cigarette dependence is the FTCD 30, 31, 32, 33, while the biochemical marker of expired carbon monoxide (CO) 34, 35 and urge to smoke 36, 37 are also used commonly to measure dependence. The Heaviness of Smoking Index HSI 38, composed of two items from the FTCD (time to first cigarette of the day and number of cigarettes usually smoked per day), has been shown to predict failure of quit attempts in non‐pregnant smokers in both population‐based 24, 37 and clinical studies 27, 31, 32, 39.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has shown that the Fagerström Test for Nicotine Dependence (FTND; Heatherton et al, 1991) has questionable psychometric properties, generally reflecting poor (Hughes, Oliveto, Riggs, Kenny, Liguori et al, 2004; Etter, Vu Da, & Perneger, 1999) to mediocre (Burling & Burling, 2003) properties of reliability and validity. The FTND has been shown to have poor internal consistency (Burling & Burling, 2003; Heatherton et al, 1991; Payne, et al, 1994; Pomerleau, et al 1994; Sledjeski et al, 2007; Steinberg, Williams, Steinberg, Krejci & Ziedonis, 2005), low construct validity (Etter et al, 1999), and poor predictive validity (Sledjeski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%